Epidemiological profile of SARS-CoV-2 in Mauritania - Ahmed, Khadijetou; Mohamed Mahmoud, Sidi M; Hamed, Cheikh T; Ahmed, Mohamed LCB; Mohamed Abdellhi, Mohamed Vall (The Journal of Infection in Developing Countries, 2025)
Introduction: This study was conducted with a profound sense of urgency and has provided significant results that will complement previous studies carried out in Mauritania—a country with unique socio-economic and healthcare characteristics—to monitor the epidemiological situation of coronavirus disease 2019 (COVID-19). The study aimed to comprehensively and rigorously investigate the epidemiological profile of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strains circulating in Mauritanian patients. Methodology: This descriptive study was carried out on 84 patients at the Cheikh Mohamed Ben Zayed Hospital and the National Institute of Hepato-Virology in Nouakchott. The samples were sequenced by next-generation sequencing (NGS) of the Illumina NextSeq 2000 type. The data were analyzed by the EPI Info 7 and SPSS 21 software. Results: The average age of the patients was 51 years, and the distribution of cases by age showed that the virus did not select a specific age group. The results indicated that the most frequent variant was Delta (33.33%). The death rate was very high (34.52%) compared to the national death rate, with a peak in the 58–69 years age group. Conclusions: This study provides an overview of the epidemiological characteristics of COVID-19 in Mauritania. These findings not only help identify what policies or strategies should be designed to combat the COVID-19 pandemic, but also pave the way for a more effective response to similar pandemics in the future.